Girl From Nongrim Hills - Ankush Saikia; SAIKIA (Ankush) (India Penguin Books, 2013)
Bok, a guitar player with a shillong band, has a lot on his mind. His elder brother kitdor has lost 50 lakh rupees on a trip to nagaland to purchase arms for a group of militants. Kitdor is given a week to repay the money and the only person he can turn to is his laid-back younger brother. Bok is helpless until a chance encounter with a beautiful woman provides him with a desperate solution. But fate can't be cheated and soon the hapless musician is tangled in her web of lies. He must outmanoeuvre her and the trail of politicians, militants and cops she leaves in her wake, and find the 50 lakhs in time if he is to save his brother. Dark, atmospheric and utterly gripping, the girl from nongrim hills is a superb thriller and a great shillong novel.
Keywords: Indian Fiction